2014
DOI: 10.3390/v6041540
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-Based Technologies to Alter Adenoviral Vector Tropism: Ways and Means for Systemic Treatment of Cancer

Abstract: Due to the fundamental progress in elucidating the molecular mechanisms of human diseases and the arrival of the post-genomic era, increasing numbers of therapeutic genes and cellular targets are available for gene therapy. Meanwhile, the most important challenge is to develop gene delivery vectors with high efficiency through target cell selectivity, in particular under in situ conditions. The most widely used vector system to transduce cells is based on adenovirus (Ad). Recent endeavors in the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 165 publications
0
11
0
Order By: Relevance
“…Miyabe et al (20) showed that enhancing c-di-GMP entry into cancer cells using liposomes increased its efficacy; adenovirus delivery of DGCs to tumors might function similarly by driving synthesis of c-di-GMP in cancer cells. One advantage of using adenovirus over general administration for this purpose is that modified adenovirus vectors have been constructed to target specific tissue types (66), and c-di-GMP might be directly delivered to tumor cells or other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Miyabe et al (20) showed that enhancing c-di-GMP entry into cancer cells using liposomes increased its efficacy; adenovirus delivery of DGCs to tumors might function similarly by driving synthesis of c-di-GMP in cancer cells. One advantage of using adenovirus over general administration for this purpose is that modified adenovirus vectors have been constructed to target specific tissue types (66), and c-di-GMP might be directly delivered to tumor cells or other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to hexon-based studies, keeping the structural stability in mind, small peptides are widely used. However, proteins as large as 83 amino acids have been introduced into this domain, but the viral packaging was somewhat affected [87,88,98,99]. Therefore, smaller proteins and peptides seem to be the better options.…”
Section: Detargeting Of Fibermentioning
confidence: 99%
“…Due to the abundance of CAR in many tissues, adenoviruses naturally display a broad tropism and infect a wide spectrum of cells (Chailertvanitkul and Pouton 2010;Waehler et al 2007). Thus, the most important challenge is to develop Ad-derived gene delivery systems with high efficiency through target cell selectivity, in particular under in situ conditions (Reetz et al 2014). Our recent endeavors in the generation of Ad vectors that specifically target stem/progenitor cells in the body have focused on linking selective peptides to viral particles that direct the virus to specific or yet unknown receptors on the surface of stem cells (Hildebrandt et al 2010;Schmidt et al 2007).…”
Section: Introductionmentioning
confidence: 99%